Conjugation of curcumin‐loaded lipid nanoemulsions with cell‐penetrating peptides increases their cellular uptake and enhances the anti‐inflammatory effects in endothelial cells. (8th January 2016) - Simion, Viorel; Stan, Daniela; Constantinescu, Cristina Ana; Deleanu, Mariana; Dragan, Emanuel; Tucureanu, Monica Madalina; Gan, Ana‐Maria; Butoi, Elena; Constantin, Alina; Manduteanu, Ileana; Simionescu, Maya; Calin, Manuela
Abstract: Objectives: To prepare and characterize in vitro and in vivo lipid nanoemulsions (LN) loaded with curcumin (Cm) and functionalized with a cell‐penetrating peptide. Methods: Curcumin‐loaded lipid nanoemulsions (CmLN) functionalized with a nona‐arginine peptide (R9‐CmLN) have been obtained, characterized and optimized for size, entrapment efficiency and in vitro Cm release. The interaction of R9‐CmLN with human endothelial cells (HEC) was investigated using cultured EA.hy926 cells, and in vivo biodistribution studies were performed using C57BL6 mice. Key findings: When used in therapeutically relevant concentration, R9‐CmLN have low haemolytic activity, low cytotoxicity on HEC, and show anti‐inflammatory effects by reducing the monocytes adhesion to TNF‐α activated HEC. Moreover, HEC uptake and internalization of R9‐CmLN was significantly higher compared to the non‐functionalized CmLN. In vivo biodistribution studies in mice revealed a higher accumulation of R9‐CmLN in the liver and the lungs compared to CmLN and the body clearance of the both nanoformulations after 72 h. Conclusions: Cell‐penetrating peptides‐functionalized CmLN have superior characteristics compared to their non‐functionalized counterparts: are more efficiently internalized by the cells, produces anti‐inflammatory effects in HEC and when administrated intravenously in mice exhibit increased accumulation in the liver and the lungs, suggesting their potential therapeutic applications in different inflammatory pathologies localized in the liver or the lungs.